Comparison of Kitab Kuning Learning at Pesantren Al-Atiqiyah in Sukabumi and Pesantren Falahul Ahkam in Pandeglang - Wiwaha, Rizzaldy Satria; Ramdani, Aldi (Tadris Al-’Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
The research discusses how the comparison of kitab kuning learning in Pesantren Al-Atiqiyah and Pesantren Falahul Ahkam. Kitab kuning learning is learning that is very influential on Arabic language skills and understanding of Islamic teachings. In addition, the learning of kitab kuning is very diverse, and a deep understanding is needed so that the teaching of kitab kuning can be more effective and efficient and maximize the results obtained. Therefore, this research focuses on learning the Kitab Kuning of Pesantren Al-Atiqiyah and Pesnatren Falahul Ahkam. This study aims to compare the methods and approaches of learning kitab kuning in two pesantren, namely Pesantren Al-Atiqiyah and Pesantren Falahul Ahkam. The kitab kuning, which is a traditional intellectual heritage in Islamic science, is the main focus of learning in these two educational institutions. This research focuses on the learning approach, teaching methods, and supporting and inhibiting factors in the process of learning kitab kuning. The research methodology uses a qualitative approach with in-depth interviews, observation, and document analysis as data collection techniques. The results showed differences in the approach to learning the kitab kuning between the two pesantren. Pesantren Al-Atiqiyah combines classical tradition with formal education, giving the impression of being flexible and open. Pesantren Falahul Ahkam shows a stronger emphasis on tradition in teaching methods, focusing on the Javanese language and the use of traditional methods. Differences in curriculum, the degree of flexibility of learning, the role of teachers, and students' interests contribute to shaping the different learning experiences in these two institutions. In addition, this study identified supporting and inhibiting factors in learning kitab kuning in both pesantren, including the availability of resources, teachers' qualifications, and students' motivation. In conclusion, an in-depth understanding of the different approaches to learning kitab kuning can provide valuable insights to improve the effectiveness of Islamic scholarly learning in pesantren.